PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF UNTUK MEMFASILITASI BELAJAR MANDIRI MAHASISWA CALON GURU SD PADA KONSEP BILANGAN - Gustimal Witri; Syahrilfuddin; Guslinda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
Interactive Learning Media (ILM) has been developed to represent the base of number concepts into a more interactive and meaningful learning experience. The first design of ILM is a computer-supported multimedia tool that explores number concepts within existing conceptual frameworks. Pre-service elementary teachers should be provided with learning that can optimize their understanding of number concepts. To collect and analyze data comprehensively, researchers employed the 4D development model, which includes the stages of define, design, develop, and disseminate. This 4D development model was used to describe the ILM comprehensively. Based on the data analysis, it can be concluded that ILM effectively improved pre-service teachers’ conceptual understanding and facilitated independent learning about number concepts.